Bleeding risk factors in patients with acute coronary syndrome: data from observational studies ORACUL II - V. A. Brazhnik; L. O. Minushkina; R. R. Guliev; A. O. Averkova; A. A. Rogozhina; O. S. Koroleva; E. A. Zubova; E. A. Karmanchikova; N. R. Khasanov; M. A. Chichkova; O. I. Boeva; A. S. Galyavich; et al. (Российский кардиологический журнал)
Aim. To identify the risk factors for bleeding of BARC scale 2-5 types in patients after acute coronary syndrome (ACS).Material and methods. The data of 1502 patients from the open multicenter study, ORACUL II, were used — 894 men (59,5%) and 608 women (40,5%), mean age — 65,7±12,9 years. Five hundred sixty (37,3%) patients had ACS with ST-segment elevation and 942 (62,7%) — ACS without ST-segment elevation. Bleeding was recorded in 164 patients (10,9%), including index admission — in 39 (2,6%) patients, of which severe (types 3-5) — 0,5%, significant — 1,7% (types 2-5).Results. Within a year after discharge, bleeding was observed in 126 (8,4%) patients, large — 0,8%, significant — 2,4%. The development of bleeding type 2-5 was associated with the presence of gastric ulcer and duodenal ulcer, gastrointestinal bleeding in history, decreased creatinine, hemoglobin clearance, age of patients, the use of anticoagulants in the composition of triple or double antithrombotic therapy, conducting of percutaneous interventional procedures, the presence of heart failure 2-4 Killip class at admission. ROC analysis showed that the predictive value of the ORACLE bleeding risk scale is 0,762, sensitivity — 62%, specificity — 78%.Conclusion. Thus, we based on routine clinical practice have created a simple scale for assessing the risk of bleeding in patients with ACS.